1992
DOI: 10.1115/1.2911283
|View full text |Cite
|
Sign up to set email alerts
|

Local Heat Transfer in a Rotating Serpentine Flow Passage

Abstract: An experimental study is performed on the internal cooling of a rotating serpentine flow passage of square cross section with throughflow. The test section is not proceeded by a hydrodynamic calming region, i.e., a leading arm, and is rotated at low Rossby numbers. The local heat transfer coefficients along the flow passage, including the leading wall, trailing wall, and sidewalls, are determined together with the circumferentially averaged values. The Reynolds, Rossby, and rotating Rayleigh numbers are varied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Results indicated that the 180-deg turn had positive effect on heat transfer in the turn and downstream. Yang et al (1992) [5] and Mochizuki et al (1994) [6] studied heat transfer in rotating multi-pass smooth square channels vie copper plate heating technique. They concluded that the flow exhibited strong three dimensional structure in the 180-deg bends and a significant enhancement in heat transfer performance could be observed at all sharp turns.…”
Section: Effect Of Geometrical Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results indicated that the 180-deg turn had positive effect on heat transfer in the turn and downstream. Yang et al (1992) [5] and Mochizuki et al (1994) [6] studied heat transfer in rotating multi-pass smooth square channels vie copper plate heating technique. They concluded that the flow exhibited strong three dimensional structure in the 180-deg bends and a significant enhancement in heat transfer performance could be observed at all sharp turns.…”
Section: Effect Of Geometrical Factorsmentioning
confidence: 99%
“…And thus, flow in rotating channels becomes extraordinary complicated and three-dimensional. Luckily, many investigations on rotating U-ducts have been published by many previous works over the past two decades [4][5][6][7][8][9][10][11][12][13][14][15][16][17].…”
mentioning
confidence: 99%
“…Guidez (1989), Hajek, et al (1991), Wagner, at al. (1991), Yang, et al (1992) and Mochizuki, at al. (1994) conducted experimental studies on heat transfer perfomance in rotating serpentine passages of square cross section with smooth walls.…”
Section: Introductionmentioning
confidence: 95%
“…The leading wall heat transfer is higher by 40-80% for the uniform wall heat flux condition (Case B) and by 20-40% for the condition of uneven wall temperatures (Case C) when compared with heat transfer with isothermal wall condition (Case A). Yang et al (1992) in their data for rotating serpentine square channel flow found that there is only a minor effect of rotation on the circumferentially averaged heat transfer even though there is significant redistribution of heat transfer among the leading, trailing and side walls due to rotation. A significant enhancement in heat transfer was found at the sharp turns.…”
Section: Introductionmentioning
confidence: 98%